Projetos colaborativos de P&D: estudo de rotinas de compartilhamento de conhecimento sob contexto de incerteza no polo industrial de Manaus - Fonseca, Edimilson Cavalcante da (Universidade do Vale do Rio dos Sinos, 2023)
The objective of this study was to analyze how knowledge sharing routines are mobilized according to the nature of uncertainties identified in collaborative R&D projects. To achieve this, a single case study was conducted with multiple units of analysis of collaborative R&D projects in the Manaus Industrial Pole. Data collection was carried out through semi-structured interviews based on predefined categories, content analysis, and data triangulation. The results provide contributions to the Relational View that assist researchers and managers in understanding how, where, and when knowledge sharing routines can be adopted during the innovation process. Types of uncertainties that may arise during the Research and Development (R&D) project phases and how knowledge sharing routines can deal with these uncertainties were identified. Market uncertainty is addressed by ICT managers through the mobilization of knowledge transfer routines that provide technical support to partner industries. In managerial uncertainty, knowledge transfer routines help structure talent access tools and build connections to overcome the lack of qualified human resources. In the face of institutional uncertainty, knowledge transfer routines are adopted to present data that justify the need for market-aligned policies. Technological uncertainty, perceived through low technical knowledge, involves the recombination of internal knowledge to solve technological incompatibility. Environmental uncertainty is overcome through knowledge creation routines that ensure proper elaboration of technical and legal justifications when there are supplier delays. Acceptance uncertainty is addressed through knowledge creation and transfer routines that help educate partners about the benefits of innovation. Social uncertainty is mitigated through standards and methods that reduce conflicting interests and clarify the stages of the innovation process. Time uncertainty is addressed through the mobilization of transfer, recombination, and creation routines to clarify requirements, rectify failures, and ensure project quality and deadlines. It is also tackled through knowledge transfer and recombination routines to monitor and adjust the scope of innovation, ensuring timely technological transfer. Finally, this study focused on understanding the evolution of knowledge sharing routines in R&D alliances, considering environmental dynamism. Further research is encouraged to explore other determinants of relational income and how they change throughout the life cycle of joint R&D projects, considering interdependence between partners. Other studies may adopt the Theory of Dynamic Capabilities to investigate how R&D organizations mobilize their resources in the face of risks and uncertainties, as well as adopt a processual approach to analyze the different knowledge sharing routines throughout the project development process.
Keywords: Rotinas de compartilhamento de conhecimento; Projetos de P&D; Incerteza; Polo Industrial de Manaus; Inovação; Knowledge sharing routines; R&D projects; Uncertainty; Manaus Industrial Pole; Innovation; ACCNPQ::Ciências Sociais Aplicadas::Administração